Criminal Policy for Legal Protection of Children Victims of Criminal Action of Sexual Violence in the Household - Hasibuan, Syaiful Asmi (Budapest International Research and Critics University, 2021)
This study is aimed to determine the criminal policy for legal protection of children victims of criminal action of sexual violence in the household. The type of research used is normative legal research which is carried out by examining library research using secondary data sources, both in the form of primary legal materials and secondary legal materials as well as tertiary legal materials. This study conclude that A criminal act is an act that results in a long-term negative impact on the victim, both physically and psychologically. Referring to the provisions in Article 10 of Law Number 23 of 2004 concerning the Elimination of Domestic Violence, legal protection that allows victims of a crime to be obtained, including: a. Protection from the family, police, prosecutors, courts, advocates, social institutions, or other parties, either temporarily or based on the stipulation of a protection order from the court; b. Health services according to medical needs; c. Handling specifically related to the confidentiality of the victim; d. Assistance by social workers and legal assistance at every level of the examination process in accordance with the provisions of the legislation; and e. Spiritual guidance services.